Cellular Delivery of Bioorthogonal Pretargeting Therapeutics in PSMA-Positive Prostate Cancer - Hapuarachchige, Sudath (Mol Pharm, 2019)
Prostate cancer is primarily fatal after it becomes metastatic and castration-resistant despite novel combined hormonal and chemotherapeutic regimens. Hence, new therapeutic concepts and drug delivery strategies are urgently needed for the eradication of this devastating disease. Here we report the highly specific, in situ click chemistry driven pretargeted delivery of cytotoxic drug carriers to PSMA(+) prostate cancer cells. Anti-PSMA 5D3 mAb and its F(ab′)(2) fragments were functionalized with trans-cyclooctene (TCO), labeled with a fluorophore, and used as pretargeting components. Human serum albumin (ALB) was loaded with the DM1 antitubulin agent, functionalized with PEGylated tetrazine (PEG(4)-Tz), labeled with a fluorophore, and used as the drug delivery component. The internalization kinetics of components and the therapeutic efficacy of the pretargeted click therapy were studied in PSMA(+) PC3-PIP and PSMA(−) PC3-Flu control cells. The F(ab′)(2) fragments were internalized faster than 5D3 mAb in PSMA(+) PC3-PIP cells. In the two-component pretargeted imaging study, both components were colocalized in a perinuclear location of the cytoplasm of PC3-PIP cells. Better colocalization was achieved when 5D3 mAb was used as the pretargeting component. Consecutively, the in vitro cell viability study shows a significantly higher therapeutic effect of click therapy in PC3-PIP cells when 5D3 mAb was used for pretargeting, compared to its F(ab′)(2) derivative. 5D3 mAb has a longer lifetime on the cell surface, when compared to its F(ab′)(2) analogue, enabling efficient cross-linking with the drug delivery component and increased efficacy. Pretargeting and drug delivery components were cross-linked via multiple bioorthogonal click chemistry reactions on the surface of PSMA(+) PC cells forming nanoclusters, which undergo fast cellular internalization and intracellular transport to perinuclear locations.